ENT 530 Business Model Canvas: Dolcé / Siti Su'aidah Kaiyisah Sharuddin ... [et al.] - Sharuddin, Siti Su'aidah Kaiyisah; Sherifuddin, Nur Adlyn Sofea; Damla, Nor Syafiqah; Yahya, Erissa Kystiena; Mohd Bahtiar, Nur Dini Syafiqah; Mohd Zaki, Nurul Izzah; Mohd Rosli, Nur Izzati; Jaapar, Nur Syazwien (2021)
In this study, the implementation of the business model canvas by Alexander Osterwalder will provide a better understanding on managing business. The selected business for this study is a small business called Dolcé that is owned by a young entrepreneur. Dolcé business is selling Melted Cadbury Cookies for cookie and chocolate lovers. Their goal is to introduce affordable yet delicious cookies dip in chocolate with premium ingredients that can be enjoyed and consumed by everyone. However, as an independent business they also faced problems while operating their production. For the business to run and operate smoothly, Dolcé has set their practices and implements on business by strategic marketing, and operational strategies in order to achieve their goals. The study of Business Model Canvas on the selected company will ensure a transparent understanding of the business plannings. The management of Dolcé is not only sought for profit, but they also consider the long-term of the business. Thus, it is important how the Business Model Canvas can help Dolce understand their customer’s segmentations, the brand positioning in market among existing competitors, their revenue streams flowcharts and analysis of its value proposition.